2020
DOI: 10.1007/s10940-019-09448-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Spatial Concentration of Urban Crime: An Insight from Nigeria

Abstract: Objective Research demonstrates that crime is concentrated. This finding is so consistent that David Weisburd refers to this as the "law of crime concentration at place". However, most research on crime concentration has been conducted in the US or European cities and has used secondary data sources. In this study, we examine whether the law of crime concentration applies in the context of sub-Saharan Africa using primary data. Methods A crime victimization survey was used to collect data in the city of Kaduna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…A common solution to this problem is to measure crime concentration among street segments that actually experience crime . This approach has become a mainstay of the recent literature (Ajzenman and Jaitman 2016; Andresen et al 2017; Favarin 2018; Gill et al 2017; Hibdon et al 2017; Levin et al 2017; Schnell et al 2017; Steenbeek and Weisburd 2016; Umar et al 2020; Vandeviver and Steenbeek 2019) and is often reported alongside a Gini coefficient. We note that while this approach will correct some of the upward bias in the measurement of crime concentration, appreciable bias will remain in most empirical applications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A common solution to this problem is to measure crime concentration among street segments that actually experience crime . This approach has become a mainstay of the recent literature (Ajzenman and Jaitman 2016; Andresen et al 2017; Favarin 2018; Gill et al 2017; Hibdon et al 2017; Levin et al 2017; Schnell et al 2017; Steenbeek and Weisburd 2016; Umar et al 2020; Vandeviver and Steenbeek 2019) and is often reported alongside a Gini coefficient. We note that while this approach will correct some of the upward bias in the measurement of crime concentration, appreciable bias will remain in most empirical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Given the inherent challenges in interpreting Gini coefficients, we argue that there remains a great deal of value in reporting crime concentration measures that correspond, as Weisburd proposed, to the share of places that account for a given share, typically one quarter or one half of crimes. Indeed, this remains a highly popular way to summarize crime concentration in the recent literature (Andresen et al 2017; Ajzenman and Jaitman 2016; Gill et al 2017; Hibdon et al 2017; Levin et al 2017), sometimes alongside a Gini coefficient (Favarin 2018; Schnell et al 2017; Steenbeek and Weisburd 2016; Umar et al 2020; Vandeviver and Steenbeek 2019).…”
Section: Prior Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Since then, the merits of these micro spatial scales in studying crime have been demonstrated across themes of concentration (Weisburd, 2015), stability (Andresen et al, 2017), theoretical explanation (Taylor, 2015;Weisburd et al, 2014) and policing interventions (Andresen & Weisburd, 2018). Investigations into the concentration of crime at micro-places have taken place in numerous countries, such as Italy (Favarin, 2018), South Africa (Breetzke & Edelstein, 2019), Belgium (Hardyns et al, 2019;Vandeviver & Steenbeek, 2019), Japan (Amemiya & Ohyama, 2019), and Nigeria (Umar et al, 2020) to name just a few. 2…”
Section: Spatial Scale and The Concentration Of Crimementioning
confidence: 99%
“…At different spatial scales, crime concentration (specifically, burglary and family theft) differs [16]. Researchers have found that crimes are more concentrated when smaller geographic units were used for analysis, and recent research has focused on addresses [17,18], street segments [19][20][21][22], and houses [23,24]. There is an internal relationship between drug-related crimes and geographical factors.…”
Section: Introductionmentioning
confidence: 99%